Influence of digital leadership on Malaysian public university branding: professionals’ identity as mediator - Wan Yakob, Wan Rosni; Don, Yahya (International Journal of Evaluation and Research in Education (IJERE), 2025)
The purpose of this study was to identify the influence of digital leadership on the professional identity and branding of public university education programs in Malaysia. A quantitative method was chosen in this study by using simple random sampling. The study population was 13,804 people, while the study sample was 476 students of education programs at Universiti Utara Malaysia (UUM), Universiti Tun Hussein Onn Malaysia (UTHM), Universiti Putra Malaysia (UPM) and Universiti Malaysia Sabah (UMS) involved. Data was analyzed using IBM-SPSS-Amos version 24. The results of the analysis show the digital leadership has an impact on professional identity and branding of public university education programs in Malaysia. In fact, professional identity are also partial mediators between the relationship between digital leadership and branding. The findings of this study are perceived to have the potential to impact the variable models of the study and represent one of the early research endeavors in this field, serving as a foundation for future studies. In addition, the results of this study are expected to provide new input to university management, stakeholders and investors to be used as a guide during the digital transformation process carried out on campus.